2019
DOI: 10.3390/jcm8111861
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D Influences the Clinical Presentation of Immune Thrombocytopenia in Children with Newly Diagnosed Disease

Abstract: Immune thrombocytopenia (ITP) is an acquired autoimmune disorder characterized by isolated thrombocytopenia defined as platelet count in peripheral blood <100 × 109/L. Hypovitaminosis D is very common in children with autoimmune diseases. To analyze whether hypovitaminosis D is associated with the clinical presentation of ITP in children, medical records of 45 pediatric patients with newly diagnosed immune thrombocytopenia in the coastal region of Croatia were evaluated. The severity of bleeding was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…As a glycosylated, full-length molecule, which is identical to endogenous TPO, the mechanism of rhTPO is more similar to that of natural TPO, and rhTPO shows profound effects on megakaryocyte development and platelet production. Previous studies have suggested that rhTPO markedly increases platelet counts in patients with chemotherapy-induced thrombocytopenia [ 16 ] as well as in patients with myelodysplastic syndromes and aplastic anemia [ 17 , 18 ]. Wang et al conducted a multicenter randomized controlled trial in 2012, showing that platelet counts in patients with chronic ITP increase rapidly after rhTPO treatment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a glycosylated, full-length molecule, which is identical to endogenous TPO, the mechanism of rhTPO is more similar to that of natural TPO, and rhTPO shows profound effects on megakaryocyte development and platelet production. Previous studies have suggested that rhTPO markedly increases platelet counts in patients with chemotherapy-induced thrombocytopenia [ 16 ] as well as in patients with myelodysplastic syndromes and aplastic anemia [ 17 , 18 ]. Wang et al conducted a multicenter randomized controlled trial in 2012, showing that platelet counts in patients with chronic ITP increase rapidly after rhTPO treatment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While investigations into immune functions in ITP ( 7 , 8 ), aiming for a better prediction of platelet count responses have been exploited and included in nowadays ITP management ( 9 11 ), a lack of consensus among clinical scores and use in ITP monitoring still exists ( 10 ). Several clinical scores have been developed including a combination of different already known risk factors: age, gender, presence of a previous infections or vaccination, bleeding grade, type of onset, platelet count at diagnosis ( 1 , 12 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood immune thrombocytopenia is an acquired autoimmune disease characterized by a decrease in platelet count (<100×10 9 /L) and an increased risk of bleeding. 1,2 This thrombocytopenia may be due to reduced platelet production and immune-mediated destruction, but usually involves glycoprotein autoantibodies expressed on megakaryocytes. [3][4][5] ITP is the most common hemorrhagic disease in children, accounting for one-third of hemorrhagic diseases, 6 Its onset is usually acute and short-lived, with an incidence of approximately (2~5)/10 million.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement data were expressed as mean±standard deviation (±s). The χ2 test was used to analyze the factors affecting the chronicity and effectiveness of ITP. Logistic regression analysis was performed on the age of onset, the course of first diagnosis and the first diagnosis of ALC.…”
mentioning
confidence: 99%